Analisis Pendapat Khalifah Umar Bin Khattab tentang Penundaan Penarikan Zakat Binatang Ternak Kambing yang Telah Mencapai Nisab - Munif, Ahmad (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2012)
Caliph Umar ibn al-Khat}t}ab had delayed withdrawal charity goats. Thoughthere are number of goats has reached nishab. It is applied to an area in theHejaz region whwn it was hit by drought. Of course this is being debated.Though Umar is one of the companions are known firm ini carrying out their religious duties. The results of this research are, first, the withdrawal delay zakat animals that have reached only apply to animals that have been hit by the famine years (ramadah). Umar’s policy gave alms to the people who have goats nishab number based on the condition of the person is also experiencing difficulties. One henred goat that he had no significant influence on survival at the time. Umar suspending withdrawal zakat to muzakki despite his wealth has reached nishab, due to difficulties and distress. Second, the vocabulary knowledge of fiqh, delay the withdrawal of zakat is must. Althought the jurist. Emphasizes that zakat is paid immediately. What is done by delaying the withdrawal of zakat Umar made one considered by some scholars to allow delaying the payment of zakat. And third, the condition of indonesia’s disaster-prone, makes delay the withdrawal of zakat by Umar could be pne of the considerations to delay payment of zakat to an area back to the state as usual.